Gender Diversity, Gender Dysphoria/Incongruence, and the Intersection with Autism Spectrum Disorders: An Updated Scoping Review. - Rea, Hannah M.; Øien, Roald A.; Webb, Sara Jane; Bansal, Shivam; Strang, John F.; Nordahl-Hansen, Anders (Journal of Autism & Developmental Disorders, 2026)
In several ways, 2018 represents a global pivot point in research and care related to the intersection of gender diversity and autism, reflected by the increase in the number of studies on the intersection and broadening of topics. We conducted a scoping review of the literature published between September 2018 and January 2024 to summarize recent research in the field. We compared and contrasted research trends post September 2018 to research that was summarized in previous scoping reviews (Nordahl-Hansen et al. in J Autism Develop Disord 49:1745–1748, 2019; Øien et al. J Autism Develop Disord 48(12):4028–4037, 2018. https://doi.org/10.1007/s10803-018-3843-z). We also summarized systematic reviews and meta-analyses published after 2018. Compared to previous reviews, we included more comprehensive search terms to focus on gender diversity broadly, rather than just gender dysphoria or gender identity disorder, and we included more detailed coding categories to uniquely identify shifts and continuities in research priorities over time. A total of 99 empirical research studies were published after August 2018 (the end of the search in the previous review) and through January 2024 on autism, gender diversity, and related topics were reviewed. There has been growth in the quantity and quality of studies on the intersection of autism and gender diversity, although methodological improvements are still needed and described in the current review. Future research should include more collaborations with stakeholders to set research priorities that are reflective of the communities being described.